FAITH, KNOWLEDGE AND FREEDOM OF BELIEF: OPPORTUNITIES AND LIMITATIONS IN THE MODERN WORLD - Nilufar Tulkunovna Rasulova (American Journals Publishing, 2024)
Faith plays a fundamental role in shaping every religion. Belief, in this context, refers to a person's conviction that a certain goal, idea, doctrine, or the existence of an event or entity and its characteristics are true. Trust forms the foundation of belief. However, not every belief becomes a lasting or healthy belief.Belief can exist independently of knowledge, but for it to be strong and healthy, it must be rooted in basic knowledge. This knowledge may stem from reason and logic or metaphorical evidence, such as divine revelations. Belief can be both religious and secular. While religious faith is formed through worship and belief in the supernatural, secular belief is rooted in emotional experience and scientific understanding of the world. This article explores the relationship between belief, knowledge, and faith in contemporary society, as well as the role of tolerance in promoting global peace.
Keywords: Healthy belief, religious organizations, opportunities, limitations, rights, religious tolerance, freedom of religion, international law, human rights